Narrativa jornalística e memória institucional: a Universidade de Santa Maria no jornal A Razão - Constante, Sônia Elisabete (2018)
The proposal of this research has as its theme the relation of the journalistic narrative and the institutional memory delimited empirically to the study of the journalistic narratives on the University of Santa Maria (USM) in the first two years of the decade of 1960. This delimitation has as presumption the observance of the viability of the reconstruction of the memory from the actions of the fundamental characters for the creation of the Institution in journalistic narratives. The central issue proposed to problematize the theme is defined in the question: "How do journalistic narratives, as a routine of the present, build the institutional memory of the University of Santa Maria from characters?" The aims to understend was to investigate the articulation of the characters as legitimized subjects of the University of Santa Maria in the journalistic narratives of the newspaper "A Razão", as a space for the construction of institutional memory. As a methodological course, a new method called the memory criterion of journalistic characters was established, based on a mixture of methods adopted by Communication, History and Archivology, in order to identify the characters and stories that contributed to the constitution of USM's institutional memory. As a result, the legitimized subject was identified as the main character who harmonized other narrative voices that had space in the local media of Santa Maria to support the initiative of a new Brazilian teaching institution. The Rector Founder José Mariano da Rocha Filho effectively contributed to the consolidation of the Institution in the newspaper, standing out among the others. It is concluded, therefore, that journalistic narratives can be part of the history of an institution, as a reliable document, but it is necessary to carry out correlated studies, as presented in this thesis, to verify the information made available in the media using the connectors narrative as a witness to the events that become in the present and in the future, historical facts.